Fenomena Mal bagi Masyarakat Urban di Jakarta - Amarena Nediari (Humaniora, 2013)
Mall building is a place where urban communities come together with their specific interest. People go to the mall with their independent needs without any emotional bonding between each other. As a public space, mall is trying to meet the needs of urban communities especially as an entertaining space for the visitors. Go to the mall has become a way of life in urban society, as a destination for the whole family. While on the other hand the existence of many mall building are the traits of sick city, because as a public space, city does not meet the social and environmental objectives anymore. Jakarta has more than 75 building mall, it has exceeded the limit of the population. Mall has become a phenomenon because it has met the lifestyle of urban society but on the other side mall has spent water absorption area. This disagreement about mall building requires a mall that friendly to the environment, so that the green open spaces and water absorption area can be provided or replaced as well. The next discussion is about mall that should build friendly to the environment and its importance to the urban community.